Adverse maternal outcomes among women who gave birth at public hospitals in eastern Ethiopia: a cross-sectional study - Leta, Masresha; Tura, Abera Kenay; Mezmur, Haymanot; Shiferaw, Kasiye; Assefa, Nega (Frontiers in Global Women's Health, 2025)
BackgroundAn adverse maternal outcome, such as anemia, postpartum hemorrhage, and postpartum eclampsia, poses a significant risk to women. While studies on the burden of adverse maternal outcomes have been conducted in various countries, including Ethiopia, many predictors beyond obstetric factors have not been fully explored. This study aimed to determine the magnitude and factors associated with adverse maternal outcomes among women who gave birth at selected public hospitals in eastern Ethiopia.MethodsA hospital-based cross-sectional study was conducted among 2,608 randomly selected women who gave birth in six public hospitals in eastern Ethiopia from November 2023 to March 2024. Data were collected through face-to-face interviews and clinical chart reviews. Factors associated with adverse maternal outcomes were identified using bivariable and multivariable robust Poisson regression analyses. Adjusted relative risk (ARR) with a 95% confidence interval (CI) was used to report the strength of the association. The variables with a p-value of <0.05 were considered statistically significant.ResultsThe magnitude of adverse maternal outcomes was 15.68% (95% CI: 14.70%–16.66%). A poor wealth index (ARR = 4.41; 95% CI: 3.46–5.62), having danger signs at admission (ARR = 1.86; 95% CI: 1.18–2.91), alcohol use during pregnancy (ARR = 1.86; 95% CI: 1.32–2.62), duration of labor ≥24 h (ARR = 1.69; 95% CI: 1.00–2.85), and maternal age greater than 35 years (ARR = 1.39; 95% CI: 1.03–1.86) increased the risk of adverse maternal outcomes. In contrast, folic acid intake during pregnancy (ARR = 0.47; 95% CI: 0.38–0.57), having partner support (ARR = 0.70; 95% CI: 0.59–0.83), and spontaneous vaginal delivery (ARR = 0.58; 95% CI: 0.49–0.68) reduced the risk of adverse maternal outcomes.ConclusionOne in six women who gave birth in eastern Ethiopia experienced adverse maternal outcomes. This rate was determined to be moderate when compared to the WHO projections for lower- and middle-income countries and better than the higher averages reported by the WHO. Targeted intervention programs, such as targeted education and empowerment programs, and the strengthening of the community health worker program would help address socioeconomic disparities and improve early detection and management of danger signs during pregnancy, which would aid in averting the occurrence of adverse outcomes.